RNA-Guided Cas9-Induced Mutagenesis in Tobacco Followed by Efficient Genetic Fixation in Doubled Haploid Plants - Schedel, Sindy; Pencs, Stefanie; Hensel, Götz; Müller, Andrea; Rutten, Twan; Kumlehn, Jochen (Frontiers in Plant Science, 2017)
Customizable endonucleases are providing an effective tool for genome engineering. The resulting primary transgenic individuals (T0) are typically heterozygous and/or chimeric with respect to any mutations induced. To generate genetically fixed mutants, they are conventionally allowed to self-pollinate, a procedure which segregates individuals into mutant heterozygotes/homozygotes and wild types. The chances of recovering homozygous mutants among the progeny depend not only on meiotic segregation but also on the frequency of mutated germline cells in the chimeric mother plant. In Nicotiana species, the heritability of Cas9-induced mutations has not been demonstrated yet. RNA-guided Cas9 endonuclease-mediated mutagenesis was targeted to the green fluorescent protein (GFP) gene harbored by a transgenic tobacco line. Upon retransformation using a GFP-specific guide RNA/Cas9 construct, the T0 plants were allowed to either self-pollinate, or were propagated via regeneration from in vitro cultured embryogenic pollen which give rise to haploid/doubled haploid plants or from leaf explants that form plants vegetatively. Single or multiple mutations were detected in 80% of the T0 plants. About half of these mutations proved heritable via selfing. Regeneration from in vitro cultured embryogenic pollen allowed for homozygous mutants to be produced more efficiently than via sexual reproduction. Consequently, embryogenic pollen culture provides a convenient method to rapidly generate a variety of genetically fixed mutants following site-directed mutagenesis. The recovery of a mutation not found among sexually produced and analyzed progeny was shown to be achievable through vegetative plant propagation in vitro, which eventually resulted in heritability when the somatic clones were selfed. In addition, some in-frame mutations were associated with functional attenuation of the target gene rather than its full knock-out. The generation of mutants with compromised rather than abolished gene functionality holds promise for future approaches to the conclusive functional validation of genes which are indispensible for the plant.